Carrier estimations in Duchenne muscular dystrophy families in Northern Ireland using RFLP analysis. Issue 2 (February 1990) - Kelly, E D; Graham, C A; Hill, A J; Nevin, N C
Abstract : Intragenic RFLP analysis was used to provide carrier risk estimations on 100 possible female carriers from 22 Duchenne muscular dystrophy families. This enabled 78% of possible carriers to be assigned high or low risks (greater than 90% or less than 10%) as opposed to 26% assigned low risk on pedigree data alone. When a single polymorphism is not informative the use of haplotype analysis for carrier estimations is illustrated for one family.